Odredbenice modeliranja suvremenoga tarifnog sustava u telekomunikacijskom prometu - Jaram, Slavko (Promet - Traffic&Transportation, 2012)
It is necessary to continually coordinate the tariff .system in telecommunication traffic with the engineering and technological developments in the field of telecommunications and the reached development stage of the telecommunications network of a coolly. The paper deals with the guidelines of essential meaning for the structuring of the tariff system being up to the level of Promet, vol. 5, 1993, br. 2, 63-67 the reached development stage of the telecommunications network. The last example of modernization of our tariff system has been discussed in a concise manner to bring it closer to the .systems of Western Europe in terms of making it more familiar to them.